Adaptive multi‐resolution framework for fast simulation of power electronic circuits. Issue 4 (30th April 2020) - Khan, Hadhiq; Bazaz, Mohammad Abid; Nahvi, Shahkar Ahmad
Abstract : An adaptive multi‐resolution simulation (AMRS) framework for fast and accurate simulation of high‐fidelity models of power electronic circuits (PECs) is presented in this study. The wide span of eigenvalues makes PEC simulation prohibitively slow. This problem can be tackled using the proposed approach. Singular perturbation approximation is used to extract simplified models by ignoring the transient contribution of the non‐dominant eigenvalues. Simplified models of different orders or resolutions, each corresponding to a particular level of accuracy are derived on the fly at no additional computational cost. The simulation engine is set such that it adaptively switches across resolutions based on a predefined tolerance during the simulation. This approach is advantageous in the sense that instead of simulating the original model over the entire time‐range, a combination of the original and simplified models is simulated. The combined use of the original and the simplified models is thus shown to be a powerful tool for efficient and accurate simulation of PECs. The examples illustrated, show that the AMRS approach makes the simulation considerably faster and ensures the complete response of the system is obtained with negligible error. The method is illustrated on a Class‐E amplifier and a DC–DC buck–boost converter.